Physiological responses of Theobroma cacao L. to water soil available in nursery stage - Jairo Garcia Lozano; Liz Patricia Moreno Fonseca (Acta Agronómica)
In the locality of El Espinal, Tolima, the effect of water stress on leaf water potential and gas exchange of plants three clones of cacao (Theobroma cacao L) was evaluated. The experiment was established in a split plot design in randomized block arrangement. The main plot was four levels of available soil water, subplot grafted seedlings to three months of three clones with five repetitions. The results showed highly significant differences (P <0.01) in content of soil water, but no differences between the materials evaluated. The loss of water in the soil decreases leaf water potential (Ψf) and causes stomatal closure altering gas exchange and vapor pressure deficit (DPV) accentuates mainly at noon with increasing evapotranspiration. The magnitude of impact of water deficit depends on climatic variations throughout the day. The climatic variables that affect plant development, are temperature and relative humidity in the form of DPV. Net photosynthesis and growth of cocoa seedlings are physiological variables very sensitive to excess and especially to water deficit.